A Note on Air-layering of Pinus pseudostrobus - Chandra, J. P. (Indian Forester, 1975)
Air-layering of Pinus pseudostrobus done in February, March, May and June failed to produce rooted air-1ayer. Air-layering done in April produced 7.5 percent rooted air-layers in control and 15 percent rooted air-layers with the help of Rootone. April is tbe proper month for air-layering of P. psuedostrobus.